2012
DOI: 10.1292/jvms.12-0111
|View full text |Cite
|
Sign up to set email alerts
|

Persorption of IgG-Fc-Coated Particulates from Intestinal Lumen into Portal Blood via Villous Columnar Epithelial Cells in Rat Small Intestine

Abstract: ABSTRACT. Previously, the specific antibody-mediated persorption of antigenic molecules and particulates from the small-intestinal lumen into the peripheral blood was clarified in rats, but the intermediation of the receptor for the specific antibodies was not. In this study, the existence of receptor for the specific antibody was experimentally examined in the rat small intestine. Glutaraldehyde-fixed sheep erythrocytes (SEs) coated by Fc-fragments of IgG (IgG-Fc), (Fab′) 2 -fragments of IgG (IgG-Fab) or bovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The number of persorbed particulates from the intestinal lumen is significantly greater in the portal blood than in the systemic circulating blood in rats [39]. Moreover, the direct crossing of the endothelium by sBCs has been histologically demonstrated by luminal administration of IgG-Fc fragment-coated particulates into the rat jejunum [40]. In the present study, the number of chylomicrons in the venules of the intestinal villi was greater than that in the arterioles in the submucosa.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…The number of persorbed particulates from the intestinal lumen is significantly greater in the portal blood than in the systemic circulating blood in rats [39]. Moreover, the direct crossing of the endothelium by sBCs has been histologically demonstrated by luminal administration of IgG-Fc fragment-coated particulates into the rat jejunum [40]. In the present study, the number of chylomicrons in the venules of the intestinal villi was greater than that in the arterioles in the submucosa.…”
Section: Discussionmentioning
confidence: 48%
“…On the other hand, a phenomenon known as “persorption,” by which various substances or particulates in the intestinal lumen are directly transported into the blood circulation without any digestion, has been reported in humans and various animal species [34]. In persorption, both specific antibodies against the ingested substances and epithelial receptors for IgG-Fc fragments probably play an important role [38,39,40]. Furthermore, the direct entry of luminal particulates into the sBCs has been histologically demonstrated in intestinal villi of the rat jejunum [40].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the affinity of receptors to Fc fragments of IgG is important for apical endocytosis. Indeed, IgG-Fc-coated particulates, including even erythrocytes, are subjected to persorption from intestinal lumen via villous columnar epithelial cells in the small intestine [63]. In early embryonic development, access of maternally deposited nuclear proteins to the genome is temporally ordered via importin affinities [64].…”
Section: Discussionmentioning
confidence: 99%
“…However, although earlier studies suggested an association of apoptosis with persorption by morphologic appearance, GAP formation was not associated with goblet cell apoptosis as determined by immunofluorescence staining 39 . In addition, it has been observed that persorption was increased by antibody coating, suggesting that although this process may not require antibody coating, it may be facilitated by fragment crystallizable region (Fc)-receptor binding, 71 a process that has not been evaluated in antigen delivery by GAPs. In support of a link between persorption and GAP formation, persorption was inhibited by the panmuscarinic receptor agonist atropine and further induced by the acetylcholinesterase inhibitor prostigmine, 65 which increases acetylcholine levels.…”
Section: A Potential Link Between Gaps and Early Observations Of Macrmentioning
confidence: 92%